Study The Integrated Pest Management on Chili Cultivation to Control Aphis gossypii and Bemisia tabaci - Wilyus Wilyus; Novalina Novalina; Fuad Nurdiansyah (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2022)
This study was carried out to build an IPM model on chili plants to control Aphis gossypii and Bemisia tabaci. The study was conducted at the Experimental Garden of the Faculty of Agriculture, Jambi University from May to September 2018. The study was designed with two treatments, namely; The application of the chili IPM model to control A. gossypii and B. tabaci and conventional chili cultivation (chili cultivation practice by farmers), each on an area of ​​0.25 ha. Observation parameters were: population of A. gossypii, population of B. tabaci, attack of A. gossypii and B. tabaci and attack of virus . The data obtained were tabulated and calculated the percentage of A. gossypii and B. tabaci attacks, virus attacks on chili and analyzed descriptively. The results of the study showed that: 1) the initial investment of A. gossypii and B. tabaci in chili plants both on IPM and conventional land was seen in chili plants 4 weeks after planting (WAP); 2) Populations of A. gossypii and populations of B. tabaci on chili plants with the application of the IPM model up to 7 WAP end to increase, but after 7 WAP the pest population is depressed and tends to decrease rapidly. It can be concluded that the IPM model with components of chili seed selection from the field, planting corn as hedges and planting refugia can suppress the development of A. gossypii, B. tabaci and virus attacks on chili plants.